Em busca da urbanidade: uma leitura dos espaços livres públicos no sertão central cearense - Pinheiro, Antonio Auriseu Nogueira (2022)
Public open spaces are places of socialization of the people in the city. With this, the leisure and recreation areas, the tours, as well as all urban environment, should provide people the possibilities for interactions, meetings and good conditions to transit or stay in public spaces, resulting in a feeling of belonging on the part of users. Most of the Brazilian territory is composed of small and medium-sized cities. According to IBGE data (2020), 94.18% of the municipalities have a population of less than 100 thousand inhabitants. This is a considerable percentage, and it scales the relevance and visibility that should be given to these territories. Thus, this study aims to analyze the urbanity of public open spaces, through relations between spatial aspects and forms of appropriation, using the region of the Sertão Central of Ceará as a spatial cutout. The research intends to: present a synthesis of the attributes of public space evaluation that contribute to the urbanity of the place, based on works by authors that adress the theme; understand the physical and social components of squares and their surroundings, by means of case studies in two significant municipalities of the Sertão Central of Ceará - Quixadá and Solonópole; in addition to identifying the environmental preferences of users of public open spaces, in order to raise both existing problems that can be corrected, and recommendations to improve the quality of the place. Initially, a literature review was carried out, seeking relevant concepts and works on this topic. After the construction of this theoretical framework, the research was developed from four methodological steps, named as: contextualize, know, observe and talk. In the first step, we sought to obtain general data that could characterize the object under study: the region of the Sertão Central of Ceará. The second step contemplated the evaluation of morphological aspects of the urban space, having as spatial cutout two polygonal (delimited in the center of the two selected cities). The third step corresponded to an analysis of people’s interaction with space, seeking an understanding of the forms of uses and appropriations. The fourth step aimed to evaluate the perception of users, and, for this, visual selection and semi-structured interview were used as instruments, applied with the aid of virtual reality technology. With the diagnosis drawn after the application of these procedures, it was verified that the attributes related to the physical aspects of the built space do not favor the conditions of urbanity. These questions were also confirmed through the positions of the participants of the environmental perception study. It is noticed that, even so, were identified several forms of uses and appropriation of these public open spaces, as sit on the sidewalk for conversations, realization of worships in the square, in addition roads being shared by automotive and animal traction vehicles, reflecting patterns of possible uses to be visualized in small and medium-sized cities, and which consequently provide urbanity with local characteristics.